The Relationship Between Reading Interest and Critical Thinking Skills in Islamic History Learning at MTs PPP Syekh M. Muhsin - Fani Rahma Sari; Susi Herwati; Demina; Rizki Pebrina; Ridwal Trisoni (IAIN Ambon, 2025)
This research was motivated by the low reading interest of students in Islamic Cultural History (SKI) subjects, which negatively affects the development of their critical thinking skills. The study aimed to describe students’ level of reading interest, their critical thinking ability, and the relationship between the two among eighth-grade students of MTs PPP Syekh M. Muhsin. A quantitative correlational approach was employed with a total population of 30 students, all of whom were selected as the research sample using a total sampling technique. Data were collected through a reading interest questionnaire and a critical thinking essay test, and analyzed using Pearson’s product-moment correlation with SPSS version 26. The findings revealed that both reading interest and critical thinking skills were at a moderate level. The correlation coefficient (rxy) obtained was 0.781, which exceeded the rtable value of 0.361 at the 5% significance level, indicating a strong and significant relationship. Therefore, it can be concluded that there is a positive and significant correlation between reading interest and students’ critical thinking skills in SKI subjects at MTs PPP Syekh M. Muhsin. These results highlight that the higher the students’ reading interest, the better their ability to think critically, thus emphasizing the importance of strengthening literacy practices in SKI learning.